Impaired reflex responses to airway occlusion in the inspiratory muscles of asthmatic subjects. - Butler, J. E. (1996)
BACKGROUND: Asthmatic subjects have an impaired capacity to activate the diaphragm during attempted maximal inspiratory efforts. Limb muscles require reflex facilitation to achieve maximal force. The reflex responses of inspiratory muscles to airway occlusion in asthmatic subjects were measured and compared with those in non-asthmatic control subjects. METHODS: Nine healthy asthmatic subjects breathed at a constant inspiratory flow through a low resistance valve. Random inspirations were transiently occluded for 250 ms. Surface electromyographic activity (EMG) was recorded over the scalene muscles, parasternal intercostal muscles, and the lateral chest wall overlying the diaphragm. The asthmatic subjects were studied with and without bronchoconstriction. Responses were compared with data from a matched group of 12 control subjects. RESULTS: Compared with the reflex responses to airway occlusion in control subjects, the duration of the initial short latency inhibition of inspiratory muscles was prolonged by 50% in asthmatic subjects and the size of the subsequent excitation was reduced by 30%. Bronchoconstriction reduced the time to the peak of the excitatory response in asthmatic subjects, although the values remained longer than in the control subjects. CONCLUSIONS: This study reveals impaired reflex excitation of inspiratory motoneurones in asthmatic subjects which could contribute to the reduced ability of these subjects to drive the diaphragm during maximal volitional efforts.